Characterization of Zn-Mg-Al Based Drosses from the Continuous Galvanizing - Blašková, Katarína; Trpčevská, Jarmila; Kuchárová, Mária (Manufacturing Technology Journal, 2016)
The present paper deals with the microstructure characterization of drosses originated during production of a new type of coating called Zinkomag. This coating creates during continuous galvanizing process and it is characterized by addition of 0.8 - 1.0 wt. % Mg and 0.8 - 1.0 wt. % Al in the zinc galvanizing bath. The addition of magnesium in such coatings leads to increasing of hardness, corrosion resistance, and better color adhesion than most common used coatings (GI coatings). In this paper drosses were investigated using AAS, LM, SEM with EDX microanalysis, and XRD.
Keywords: CGL; Zinkomag; Coating; Dross; Structure